O coletivo fora do eixo : juventude organizada, produção, circulação e consumo cultural - Brasil, Wener da Silva (2015)
In this research seek to conduct a study on the performance of the Coletivo Fora do Eixo as a social organization developed by young people, whose main causes culture. The aim is to describe the performance in the Coletivo Fora do Eixo network from the study of social actors that make up the group and how they build and execute actions based on the production, circulation and cultural consumption in the context of politics and economics. In this context, I analyze, from the direct observation, the interviews and analysis of applications, websites and social networks, which are the discursive strategies present in the brazilian contemporary debate about culture, give meaning to the political articulations collaboratively and as the Coletivo Fora do Eixo develops creative strategies for generation of the economy. I still intend to verify the importance of technology, based on collective intelligence, as networked information access tool. And in this way, meet the collective processes and motivating young people from different social and cultural proposals, to articulate and organize network collaboratively.